Thermal Performance of Traditional House in the Upland Central Celebes of Indonesia - Fitriaty, Puteri; Antaryama, I.G.N. Antaryama; Nastiti N.E, Sri Nastiti N.E (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2011)
House presents special problems for design in relation to climate as it accommodates variety of uses over 24-hour period. It is widely known in the tropical countries that traditional houses are more sensitive to the prevailing climate and able to provide comfortable internal environment for the occupants. Tambi as one of traditional houses in upland Central Celebes Indonesia is believed to be thermally comfortable, yet there still no empirical evidence to approve it. Present study conducted empirical studies on typical traditional Tambi houses to evaluate their thermal performance. External and internal climatic conditions were measured in each house and were analysed. Results of the study showed that typical traditional Tambi house are not able to maintain the internal temperature within the comfort range for a preiod of 24- hours. Thermal quality of the house, however, were improving as indicated by internal temperatures which were more satisfactory than the external temperatures.